2018
DOI: 10.1029/2018jd028927
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Sensitivity and Uncertainty Quantification in the Version 1 of E3SM Atmosphere Model Based on Short Perturbed Parameter Ensemble Simulations

Abstract: The atmospheric component of Energy Exascale Earth System Model version 1 has included many new features in the physics parameterizations compared to its predecessors. Potential complex nonlinear interactions among the new features create a significant challenge for understanding the model behaviors and parameter tuning. Using the one-at-a-time method, the benefit of tuning one parameter may offset the benefit of tuning another parameter, or improvement in one target variable may lead to degradation in another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 102 publications
0
96
0
Order By: Relevance
“…Yang et al (2013) also indicated the zmconv_tau was sensitive for LWCF. The autoconversion efficiency of cloud water to precipitation (zmconv_c0_lnd and zmconv_c0_ocn) and the cloud ice sedimentation velocity (cldsed_ai) were found to be sensitive for LWCF in Qian et al (2018). That is to say, all the tuning parameters in this study are very sensitive for LWCF, resulting in this field having the most improvement.…”
Section: Variablementioning
confidence: 70%
“…Yang et al (2013) also indicated the zmconv_tau was sensitive for LWCF. The autoconversion efficiency of cloud water to precipitation (zmconv_c0_lnd and zmconv_c0_ocn) and the cloud ice sedimentation velocity (cldsed_ai) were found to be sensitive for LWCF in Qian et al (2018). That is to say, all the tuning parameters in this study are very sensitive for LWCF, resulting in this field having the most improvement.…”
Section: Variablementioning
confidence: 70%
“…A detailed analysis of its cloud and convective characteristics and the rationale for model tuning are provided in Xie et al () and Zhang et al (). Sensitivity of EAM to a number of its adjustable parameters is explored in Qian et al (). EAM simulated diurnal cycle of precipitation is analyzed in Xie et al ().…”
Section: Model Overviewmentioning
confidence: 99%
“…Xie et al () provided more detailed information about the model tuning. Sensitivity of EAMv1 to a number of its adjustable parameters is explored in Qian et al (). EAMv1 simulated cloud and convective characteristics can be found in Xie et al () and Zhang et al ().…”
Section: Eamv1 and Experiments Designmentioning
confidence: 99%